(untitled) (Journal of the Society for Musicology in Ireland, 2020)
A review of Matthew Dubourg, Welcome Home, Mr Dubourg, Irish Baroque Orchestra Conducted by Peter Whelan, Linn Records (2019) (CD) CKD 532.